Innovation of “Virtual Living Room” in Improving the Quality of Public Services at the Bengkulu Food and Drug Administration: A Case Study - Novliza Eka Patrisia; Hafri Yuliani (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
This study aims to analyze the “Virtual Living Room” innovation at the Bengkulu POM Office in improving the quality of public services. The Virtual Living Room is a video conference-based consultation service that allows the public to connect directly with BPOM officers via the Zoom application without having to physically come to the office. The study uses a qualitative approach with a case study method. Data collection techniques include in-depth interviews, participatory observation, and documentation. The results of the study show that the Virtual Living Room innovation has contributed positively to improving the quality of public services, particularly in terms of ease of access, speed of response, and time efficiency. This innovation has also been expanded to the MPPs of Central Bengkulu and North Bengkulu Regencies. Challenges faced include public digital literacy, network infrastructure, and suboptimal socialization. The study recommends strengthening the capacity of officers, optimizing socialization, and developing service features to ensure the sustainability of the innovation.